MODEL KINERJA BERBASIS NILAI-NILAI BUDAYA ORGANISASI PADA PEGAWAI KANWIL KEMENTERIAN AGAMA PROVINSI BANTEN - Dinantara, Mohamad Duddy; Harras, Hadyati (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
Building public trust is the core of public services, but currently at the Regional Office of Banten Religion Ministry, public trust has not been built. The negative stigma of society, such as lack of transparency, many civil servants who act on behalf of religion take advantage of the public's ignorance on Hajj and Umrah management, and poor management of religious education. Therefore, this study was conducted seeing to what extent the employees of Banten Religion Ministry performed, and to analyze work culture factors had an impact on performance. This study uses quantitative methods, research sample is 67 respondents, sampling technique is simple random, research instrument uses a questionnaire, and the analysis method uses linear regression. The results showed that professional work culture contributed dominantly to performance. This finding confirms that the professional working model in the Banten Religion Ministry is more prominent than other cultural values